Persistent catheter-related Staphylococcus aureus bacteremia after catheter removal and initiation of antimicrobial therapy. - Ki-Ho Park; Yu-Mi Lee; Hyo-Lim Hong; Tark Kim; Hyun Jung Park; So-Youn Park; Song Mi Moon; Yong Pil Chong; Sung-Han Kim; Sang-Oh Lee; Sang-Ho Choi; Jin-Yong Jeong; et al. (PLoS ONE, 2012)
OBJECTIVES: Catheter-related Staphylococcus aureus bacteremia (CRSAB) occasionally persists despite catheter removal and initiation of appropriate antimicrobial therapy. The aim of this study was to determine the incidence, risk factors, and outcomes of persistent CRSAB after catheter removal and initiation of antimicrobial therapy. METHODS: Consecutive patients with CRSAB were prospectively included from over a 41-month period. We compared the clinical features, 40 bacterial virulence genes, and outcomes between patients with persistent CRSAB (i.e., bacteremia for >3 days after catheter removal and initiation of appropriate antimicrobial therapy) and non-persistent CRSAB. RESULTS: Among the 220 episodes of CRSAB, the catheter was kept in place in 17 (6%) and removed in 203 (94%) cases. In 43 (21%) of the 203 episodes, bacteremia persisted for >3 days after catheter removal and initiation of antimicrobial therapy. Methicillin resistance (Odds ratio [OR], 9.01; 95% confidence interval [CI], 3.05-26.61; P<0.001), non-catheter prosthetic devices (OR, 5.37; 95% CI, 1.62-17.80; P=0.006), and renal failure (OR, 3.23; 95% CI, 1.48-7.08; P=0.003) were independently associated with persistent CRSAB. Patients with persistent CRSAB were more like to experience complication than were those with non-persistent CRSAB (72% vs. 15%; P<0.001). Among all episodes due to methicillin-resistant S. aureus, persistent CRSAB isolates were associated with accessory gene regulator (agr) group II (P= .04), but presence of other bacterial virulence genes, distribution of vancomycin minimum inhibitory concentration distribution, and frequency of vancomycin heteroresistance did not differ between the groups. CONCLUSIONS: In patients with CRSAB, bacteremia persisted in 21% of cases despite catheter removal and initiation of antimicrobial therapy. Methicillin resistance, renal failure, and non-catheter prosthetic devices were independent risk factors for persistent CRSAB, which was associated with a higher rate of complications.